(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The surge in global electronic waste (e-waste) due to technological advancements is exacerbated by India’s increasing contribution. This study explores the geographical dimensions of e-waste in India, analyzing factors influencing its generation, disposal, and associated environmental and social implications.